OPENING UP POTENTIAL: TURNING WONODADI KULON VILLAGE INTO A THRIVING WATERSPORTS PARADISE: MEMBUKA POTENSI: MENGUBAH DESA WONODADI KULON MENJADI SURGA OLAHRAGA AIR SUNGAI YANG BERKEMBANG - Margisal Utomo, Gatot; Fefrian Rosmi, Yandika; Akbar Harmono, Bayu; Hakim, Luqmanul; Bripandika Putra, Ismawandi; Kurnia Darisman, Eka (Antis-publisher, 2024)
Research shows that the management of natural tourist attractions in Pacitan Regency is running well, as the government has provided supporting facilities and infrastructure, but there are shortcomings, such as promotion which is still not very advanced because it still uses print media, road access to the location is not good and the budget is still limited. The PPM team of Physical Education Lecturers socialized the government of Wonodadi Kulon Village, Ngadirojo District, Pacitan Regency to promote river water sports-based tourism through social media and conduct comparative studies to other tourist villages. The method used in community service program activities is based on the asset based approach (ABA). The activity stages include field observations, drafting material requirements and implementation, licensing, implementation of service, evaluation, up to the final report. Based on the results and discussion that have been described, it can be concluded that Wonodadi Kulon Village, Ngadirojo District, Pacitan Regency has the potential to be developed as a village tourism based on river water sports. In this PPM Program, activities include determining appropriate strategies to improve the welfare of village communities through river water sports-based tourism, training and mentoring which contains the required materials including various types of river water sports, management, water sports facilities and infrastructure, prevention. and first aid for accidents, publicity and marketing using social media. Where the results of the training and mentoring can encourage participants to play a role together in the future in managing village tourism based on river water sports as a form of utilizing the natural wealth in the village.